1998
DOI: 10.1021/tx980038d
|View full text |Cite
|
Sign up to set email alerts
|

Deamination and Dimroth Rearrangement of Deoxyadenosine−Styrene Oxide Adducts in DNA

Abstract: In reactions between styrene oxide and the ring nitrogen at the 1-position of deoxyadenosine, the epoxide is opened at both the alpha- (benzylic) and beta-carbons. The 1-substituted nucleosides formed are unstable and subsequently undergo either Dimroth rearrangement to give N6-substituted deoxyadenosines or deamination to give 1-substituted deoxyinosines. alphaN6-Substituted compounds are also formed from direct reaction at the exocyclic nitrogen. Kinetic experiments revealed that relative rates of deaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…Analytical runs were performed on a 4.6 mm × 250 mm YMC-ODS-AQ column at a flow rate of 1.0 mL/min; preparative-scale isolations were carried out on a 10 mm × 250 mm YMC-ODS-AQ column at a flow rate of 3.0 mL/min. The structure and stereochemistry of the styrene oxide adducts were confirmed by independent syntheses from 6-chloropurine 2′-deoxyriboside and (R)-and (S)-2-amino-2-phenylethanol (9) for the R adducts and (R)-and (S)-2-amino-1-phenylethanol (10) for the adducts and also by comparison with literature values (6,11).…”
Section: Introductionmentioning
confidence: 53%
“…Analytical runs were performed on a 4.6 mm × 250 mm YMC-ODS-AQ column at a flow rate of 1.0 mL/min; preparative-scale isolations were carried out on a 10 mm × 250 mm YMC-ODS-AQ column at a flow rate of 3.0 mL/min. The structure and stereochemistry of the styrene oxide adducts were confirmed by independent syntheses from 6-chloropurine 2′-deoxyriboside and (R)-and (S)-2-amino-2-phenylethanol (9) for the R adducts and (R)-and (S)-2-amino-1-phenylethanol (10) for the adducts and also by comparison with literature values (6,11).…”
Section: Introductionmentioning
confidence: 53%
“…Studies with epoxides containing substituents capable of delocalizing positive charge by conjugation, such as styrene oxide and butadiene monoepoxide, show that direct alkylation of the N 6 -position of adenosine occurs mainly on the internal oxirane carbon, predominantly by a S N 1 mechanism (as reviewed in 36). In contrast, it was demonstrated that N 6 - dAdo adducts on the terminal oxirane carbon of styrene oxide were exclusively formed by Dimroth rearrangement of N1-dAdo adducts (40;54). …”
Section: Discussionmentioning
confidence: 97%
“…[17] We did not observe any ring opening adducts from the β attack of 2 or deamination of 4 to form an N1-inosine adduct, which has been reported in the reaction of styrene oxide with 2Ј-deoxyadenosine. [23][24][25] The lack of a phenyl or vinyl group on the α-carbon atom of an oxiran to stabilize the carbocation intermediate of an S N 1 reaction of 2 explains why no β attack and only γ attack adducts were observed; furthermore, the γ-position of 2 is sterically less hindered than the β-position. The secondary hydroxy group on the β-carbon atom of 4 cannot form an oxazolinium ring to facilitate the deamination process, therefore, the deamination product of 4 was not observed.…”
Section: Reaction Of 2 Withmentioning
confidence: 99%
“…[17,[23][24][25] The transformation of 4 (an N1 adduct) to 5 (an N 6 adduct) by Dimroth rearrangement was monitored with a reversephase HPLC system, which showed that 4 had a half life of ca. 24 h in K 2 HPO 4 buffer solution at 37°C.…”
Section: Rearrangement Of 4 Tomentioning
confidence: 99%